A new approach to a practical subwavelength resolving microscope - Fiddy, Michael A. (2013)
Superresolution depends on near-field capture and transfer of high spatial frequencies from the scattering object. These evanescent waves are transferred to a near-field image domain using a negative index material. Measuring images with subwavelength scale resolution in the near field by scanning is not practical and ignores inevitable object–lens–image coupling phenomena as well as the need to employ inverse scattering algorithms. An alternative approach based on compressive sampling permits the use of a single fixed detector. Traditionally, in such a system, an image-bearing wavefront is projected onto a series of patterns (= basis functions) and the transmitted light integrated by a lens onto a single-point detector. Image reconstruction is possible by weighting each basis function with its measured coefficient and summing, including basis functions representing evanescent waves. We employ a single fixed detector in the back focal plane of a negative index concave lens and basis functions realized by structured illumination from combinations of a set of discrete sources. We have investigated this as an approach to recover subwavelength scale details about a scattering object and report our results.